Comparative Genomic and Phylogenomic Analyses Clarify Relationships Within and Between Bacillus cereus and Bacillus thuringiensis: Proposal for the Recognition of Two Bacillus thuringiensis Genomovars - Baek, Inwoo; Lee, Kihyun; Goodfellow, Michael; Chun, Jongsik (Frontiers in Microbiology, 2019)
The present study was designed to clarify the taxonomic status of two species classified as Bacillus cereus sensu lato, namely Bacillus cereus sensu stricto and Bacillus thuringiensis. To this end, nearly nine hundred whole genome sequences of strains assigned to these taxa were the subject of comparative genomic and phylogenomic analyses. A phylogenomic tree based on core gene sequences showed that the type strains of Bacillus cereus and Bacillus thuringiensis formed a well-supported subclade separated from subclades composed of the remaining validly published Bacillus cereus sensu lato species. Comprehensive comparative genomics clearly showed that the distribution of pesticidal genes is irregular, which means that the strains identified as Bacillus thuringiensis formed polyphyletic clades. These results when taken together with those from a host of previous studies clearly show that B. cereus sensu stricto and B. thuringiensis stains should be classified in the same species. Consequently, it is proposed that Bacillus thuringiensis Berliner 1918 be recognized as a heterotypic synonym of Bacillus cereus Frankland and Frankland 1887; an emended description is given for the latter. The constituent strains assigned to the emended species were recovered in three subclades which were designated as Bacillus cereus genomovar cereus, Bacillus cereus genomovar nebrakensis and Bacillus cereus genomovar thuringiensis based on overall genome sequence similarities.